Analysis of Factors Affecting Employee Performance at Bontosikuyu Sub-District Office, Selayar Islands Regency - Andi Agusniati (Journal of Entrepreneur, Business and Management, 2023)
The purpose of this study was to determine the partial and simultaneous influence of the variables studied, where this study used a quantitative approach with a sample of 38 people with multiple regression analysis methods including validity tests, reliability tests, partial and simultaneous hypothesis tests with the help of the SPSS 25 application. The results of this study show that there is a positive and significant influence of leadership style on employee performance. And simultaneously, the regression coefficient values of Organizational Culture, Organizational Commitment and Leadership Style have a positive and significant effect on Employee Performance. Keywords: Organizational Culture, Organizational Commitment, Leadership Style, Employee Performance